Training and mentoring for the business process of the Nile Tilapia Processing Center “Sandara” Lumbok Seminung West Lampung - Febrianty Febrianty; Divianto Divianto (Borneo Novelty Publishing, 2025)
The Sandya Darya Urgha (Sandara) Tilapia Processing Center, located in Lumbok Seminung, West Lampung, is a fisheries-based community empowerment initiative designed to enhance the quality and competitiveness of processed tilapia products. The training and mentoring program implemented at this center aims to develop the technical skills of the local community in tilapia processing while introducing efficient and safe processing technologies. The program covers various aspects, including the tilapia production process, modern processing techniques, business management, and food safety standards. In addition to training, direct mentoring is provided to ensure the proper application of processing techniques and to enhance production capacity. The impact of this initiative has been significant, leading to improved product quality, expanded market access, and increased economic welfare for the local community. By adding value to tilapia processing, this initiative is expected to contribute to reducing unemployment and strengthening the fisheries sector in West Lampung.